2022
DOI: 10.3389/fcimb.2022.873161
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Pathogenic Bacteria Causing Descending Necrotizing Mediastinitis

Abstract: The combination of maxillofacial infections (MI) with descending necrotizing mediastinitis (DNM) is a complex disease characterized by rapid development and high mortality. Here, we performed metagenomic next-generation sequencing (mNGS) using samples from 21 patients with MI and eight patients with DNM. In this study, we found that the species richness of the DNM group was higher than that of the MI group, and the species diversity of the DNM group was higher than that of the MI group, with no statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
3
1
1
Order By: Relevance
“…The sensitivity test of pathogens can provide important guidance for subsequent antibiotic use. Our study found that the most frequent pathogens were S. constellatus and A. baumannii , while in a study for patients with DNM, the dominant species were Prevotella oris and S. constellatus ( 20 ). Therefore, collection of multiple abscess samples during surgery is recommended to identify the causative pathogens.…”
Section: Discussioncontrasting
confidence: 46%
“…The sensitivity test of pathogens can provide important guidance for subsequent antibiotic use. Our study found that the most frequent pathogens were S. constellatus and A. baumannii , while in a study for patients with DNM, the dominant species were Prevotella oris and S. constellatus ( 20 ). Therefore, collection of multiple abscess samples during surgery is recommended to identify the causative pathogens.…”
Section: Discussioncontrasting
confidence: 46%
“…Mogibacterium and Denitratisoma have been identified as potential causative agents of gingival disease ( Liu et al, 2023 ; Wu et al, 2023 ). Mogibacterium is also associated with intermaxillary gap infections ( Sun et al, 2022 ). Denitratisoma is involved in denitrification and are used in sewage treatment ( Wang et al, 2023 ), but their role in the gut requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This rare but fatal illness involves a severe soft tissue infection that progresses along the fascia to the mediastinum [4]. The dissemination of the DNI to the mediastinum can be facilitated by gravity, the pressure of the abscess, and negative thoracic pressure during respiration [41]. The symptoms of descending mediastinitis include odynodysphagia, dyspnea, respiratory distress, chest discomfort, and fever, even though the patients would not necessarily present these clinical manifestations [42].…”
Section: Discussionmentioning
confidence: 99%